Factors associated with body weight status among Iranian students in a Malaysian public university - Mokhtari, Tahereh (2014)
University students are essential targets for the elevation of healthful lifestyles due to the fact that they help produce findings that can diminish the risks of lifestyle disorders later in life. The weight statuses of these students are believed to be greatly influenced by socio-demographic, lifestyle, dietary and psychological factors. The main aim of this study therefore, was to bring to light the associations between the above-mentioned factors and university students’ weight statuses. The 311 participants of this study were selected through simple random sampling method and the data was collected through a questionnaire comprising 4 sections aimed at identifying the participants’ demographic factors, smoking status, physical activity level, dietary intake, dietary pattern, depression and anxiety levels. The results of the study indicated that there was significant associations between BMI and energy intake (r= 0.281, p =0.000), carbohydrate (r= 0.310, p =0.000), protein (r= 0.208, p=0.000), fat (r= 0.198, p =0.000), western dietary pattern (r = 0.13; p =0.01), physical activity (r= -0.14; p = 0.009), anxiety (r = - 0.15; p ≤ 0.01), age (r = 0.19; p ≤ 0.01),gender (χ2 = 43.03, p=0.001), marital status (χ2 = 8.8, p=0.03) and income level (r =0.22; p ≤ = 0.01) of the students. Multivariate regression analysis for the prediction of body weight status demonstrated that gender, carbohydrate intake, age, physical activity, anxiety, income level, mix dietary pattern and smoking status had significant effects on BMI. In conclusion, the etiology of obesity and overweight is complex and a large number of factors affected BMI including energy intake, physical activity, psychological status, environment, culture and economic status. Investigation of the factors associated with body weight status is a necessary consideration in planning obesity interventions.